Corporate Social Responsibility and Corporate Image: a Survey on Denpasar City Community (E-Jurnal Akuntansi, 2024)
The company carries out corporate social responsibility (CSR) to improve the company's image (corporate image). CSR is carried out with community support, environment, product and diversity. This study aims to determine The Influence of Corporate Social Responsibility on Corporate Image at PT. BPR Lestari (Survey on Denpasar City Community). The sampling technique used was nonprobability sampling with the convenience sampling method. Methods of data collection using a questionnaire, from as many as 400 respondents. The analysis technique used is multiple linear regression. The results of the analysis show that CSR in community support, environment, product, and diversity variables has a positive effect on corporate image
Keywords: Corporate Social Responsibility; Community Support; Environment; Product; Diversity; Corporate Image